2014
DOI: 10.1093/rheumatology/keu444
|View full text |Cite
|
Sign up to set email alerts
|

An outsourced health-enhancing physical activity programme for people with rheumatoid arthritis: exploration of adherence and response

Abstract: Objectives. The aims of this study were to document adherence to and changes in health-enhancing physical activity (HEPA) levels and self-reported and assessed functioning and to explore aspects of adherence and response during the first year of an outsourced 2-year HEPA programme in people with RA.Methods. Two-hundred and twenty patients participated in this observational cohort study, which included daily physical activity, twice-weekly circuit training and biweekly support group meetings. Self-reported data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 38 publications
1
55
0
Order By: Relevance
“…Third, 2 years’ supported physical activity improved the ventricular‐arterial coupling. Taken together, these results indicate that improved arterial and cardiac function over time are interconnected, and may contribute to the beneficial effects of physical activity in patients with RA even in individuals without apparent CVD.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Third, 2 years’ supported physical activity improved the ventricular‐arterial coupling. Taken together, these results indicate that improved arterial and cardiac function over time are interconnected, and may contribute to the beneficial effects of physical activity in patients with RA even in individuals without apparent CVD.…”
Section: Discussionmentioning
confidence: 65%
“…The physical activity support programme has been described in detail in previous reports from PARA 2010 . In brief, participants were encouraged to perform moderate‐intensity physical activity for 30 min on most days of the week for 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 presents all the articles that were selected for this systematic review. Of the 37 articles reviewed focused on clarifying the relationship between fitness parameters and exercise self-efficacy, 32 articles were focused on populations with some type of pathology [ 6 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Five articles focused on the pathology-free middle-aged population [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…A two-year program of Physical Activity in RA (PARA) 2010 was designed to investigate its feasibility and to study changes in self-reported variables, physical capacity measurements, in ammation, pain modulation and cardiovascular risk 11 . Positive changes during the two-year study period were observed for HEPA participants concerning symptoms and physical capacity [12][13] and cardiovascular risk factors [14][15] , while pain modulation did not change 16 . In this context we performed a pilot study with focus on protein adaptations in muscle tissue in a subgroup of people with RA who consented to repeated muscle biopsies.…”
Section: Introductionmentioning
confidence: 89%
“…Participants in the PARA 2010 study were recruited from the Swedish Rheumatology Quality registers (SRQ). They were asked to participate in a two-year program aimed to increase and maintain HEPA levels among people with RA in line with public health recommendations [11][12][13] For this sub-study six women who consented to donate muscle biopsies at baseline, at one-and two-year follow-ups were included. The participants were independent in daily living, interested in physical activity support, uent in Swedish, not already obtaining HEPA as per recommendations and without major diseases preventing HEPA 11 .…”
Section: Participants and Samplesmentioning
confidence: 99%